Neurological Complications in Aortic Valve Surgery and Rehabilitation Treatment Used - Sanz-Ayan, M. Paz; Diaz, Delia; Martinez-Salio, Antonio; Garzon, Francisco Miguel; Urbaneja, Carmen; Valdivia, Jose; Forteza, Alberto (IntechOpen, 2011)
None